Information asymmetry, mutual funds and earnings management: Evidence from China - Yunhao Dai; Dongmin Kong; Li Wang (China Journal of Accounting Research, 2013)
This paper investigates how information asymmetry and mutual fund ownership affect listed companies' earnings management. We show that (1) reducing information asymmetry improves firms' earnings management behavior; (2) relative to short-term mutual funds, long-term mutual funds promote earnings quality by adopting a monitoring role; and (3) by dividing firms into high/low information asymmetry groups, we find that the information environment significantly increases the effect of long-term mutual funds on firms' earnings management. In this paper, we provide new evidence for the role that institutional investors play in a typical emerging capital market. Our results have clear policy implications: to increase earnings quality, it is essential to improve information transparency and develop long-term institutional investors.
Keywords: G12; G14; G18; M41; 650; Information asymmetry; Mutual funds; Earnings management